MANAJEMEN KURIKULUM VOKASIONAL TERHADAP ENTREPRENEUR SISWA SMKS ULUMUDDIN LHOKSEUMAWE - Heldiana, Heldiana; Yusrianti, Susi; Yuliza, Yuliza (Hijri, 2023)
This research explores vocational curriculum management for student entrepreneurship at SMKS Ulumuddin, Lhokseumawe, using a qualitative descriptive approach. The study delves into curriculum planning, organization, and implementation for student entrepreneurship. Findings reveal the formulation of the school's vision, mission, objectives, tailored implementation plans, and the establishment of a curriculum development team and competence assessment team. The vocational curriculum focuses on meeting students' skill development needs, utilizing practical activities, teaching factory methods, and scheduled work experiences. Evaluation occurs at micro and macro-levels, assessing students' competence with input from stakeholders and external assessors. The head of the school is supported by senior teachers in continuous curriculum development evaluation. The study also highlights the formation of students' entrepreneurial character, achieved through integrating productive subjects, creative entrepreneurial products, PSG implementation, and student immersion in designated areas. Additionally, the research identifies obstacles and supporting factors impacting the vocational curriculum's success, including human resources, teaching methods, facilities, and understanding of industry and entrepreneurship. Overall, the study provides valuable insights into vocational curriculum management, offering guidance on how to foster entrepreneurial skills among students effectively.